Fast ibuprofen, ketoprofen and naproxen simultaneous determination in human serum for clinical toxicology by GC-FID - Hložek, Tomáš; Bursová, Miroslava; Cabala, Radomír (Clinical biochemistry, 2014)
OBJECTIVES: The aim of this study was to develop and validate a gas chromatographic method with flame ionization detection (GC-FID) for the measurement of ibuprofen, naproxen and ketoprofen for clinical toxicology purposes. DESIGN AND METHODS: 100μL of plasma was treated with methyl chloroformate and derivatized analytes were extracted with hexane. Optimal conditions of the derivatization procedure have been found using the experimental chemometric design (face-centered central composite design). The selectivity and efficiency of the procedure was confirmed by GC-MS. RESULTS: The assay was linear in the concentration range of 10-400μgmL(-1), with adequate accuracy and precision for GC-FID (98-106.7%, CV≤9.1%, respectively) and for GC-MS (99.3-105.5%, CV≤9.2%, respectively). CONCLUSION: The entire sample preparation procedure is completed within 5 min and the quantitative results are available within 35 min. The method was successfully applied to quantify the selected compounds in serum of patients from emergency units.
Keywords: Ibuprofen; Ketoprofen; ibuprofen; lidé; Chromatography, Gas; Naproxen; ketoprofen; chromatografie plynová; naproxen; Humans